UCI sports nutrition project: Body composition, energy requirements, and energy availability in cycling - Burke, L. M.; Gonzalez, J. T.; Areta, J. L.; Kuikman, M. A.; Coates, A. M.; Bailey, D. M.; Moran, J.; Dolan, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
Maintaining adequate energy availability is a key concern for many cyclists, many of whom must balance the need to support their very high training and competition energy expenditure while simultaneously adopting nutritional strategies that will allow them to maintain the body mass deemed most conducive to optimal performance. Available evidence indicates that cyclists tend to be a weight-conscious group that frequently reports engaging in restrictive eating behaviors. Together, the dual demands of supporting the energetic cost of their training alongside restricting energy intake to maintain a low body mass may place some riders at a high risk of experiencing negative health- and performance-related consequences associated with prolonged and problematically low energy availability. Within this review, we critically discuss issues related to the role of body mass and composition in cycling performance along with cyclists` reported perceptions on this issue. We also describe evidence on reported energy expenditure and intake in high-level cyclists, recognizing the challenges of accurate assessment of these parameters, particularly within the field setting. Evidence related to signs and signals of problematic low energy availability in cyclists is described, also recognizing the complexity of determining causality for longer term low energy availability consequences alongside identifying other potential contributory factors to the symptomatology reported for this population. Finally, we make pragmatic recommendations to support cyclists to meet their physique goals while simultaneously emphasizing and supporting longer term health, performance, and well-being.